The Effect of Organizational Capabilities on Quality of Service An Analytical Study of The Views of The Directors of The Inspector General's Office of The Ministry of Finance - Mohanad H. Yaser Al - Atawi; Mustafa Tawfeeq Zaki (مجلة الغري للعلوم الاقتصادية والادارية)
The purpose of the research is to explore the relationship between effectiveness organizational capabilities in terms of (organizational learning capabilities and knowledge management capabilities) and service quality in terms of (response, reliability, tangibility, and sympathy). The research problem if its identify several questions that will be focused on the nature of the effectiveness relationship among the variables of the search . For that the development of a hypothesis of the research reflects one main hypothesis and two sub-hypotheses. In order to verify the validity of the hypotheses , all those hypothec was subjected to multiple tests to confirm their validity. The research has used the questionnaire as a means of obtaining data. Mean while the descriptive and analytical approach are used as a research method. The sample is taken intentionally from the selecting of managers and officials at the ministry of finance inspector . General office number forty seven . The questionnaire is distributed to all of them, but only 44 respondents are prepared for statistical analysis. The results show that there is an effectiveness relationship of organizational capabilities in terms of organizational learning capabilities in improving the quality of service. Regarding knowledge management Capabilities it will not affect the improvement of service quality